2010
DOI: 10.1080/00140139.2010.513452
|View full text |Cite
|
Sign up to set email alerts
|

Process and implementation of participatory ergonomic interventions: a systematic review

Abstract: Participatory ergonomic (PE) interventions may vary in implementation. A systematic review was done to determine the evidence regarding context, barriers and facilitators to the implementation of participatory ergonomic interventions in workplaces. In total, 17 electronic databases were searched. Data on PE process and implementation were extracted from documents meeting content and quality criteria and synthesised. The search yielded 2151 references. Of these, 190 documents were relevant and 52 met content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
150
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 45 publications
3
150
0
10
Order By: Relevance
“…For instance, studies show the potential in helping to manage design information to reduce workplace risk factors for developing MSDs [21,22]. This is further accentuated by the findings of a review [15] where program support, organizational knowledge and communication are discussed as key facilitators and barriers for participatory ergonomics interventions.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, studies show the potential in helping to manage design information to reduce workplace risk factors for developing MSDs [21,22]. This is further accentuated by the findings of a review [15] where program support, organizational knowledge and communication are discussed as key facilitators and barriers for participatory ergonomics interventions.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, a review [15] reports that participatory ergonomics interventions show positive impacts, and focuses more on physical and work process changes. It also mentions that these interventions need the right practitioners to be involved, appropriate ergonomics training and clear responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Two main considerations were identified: (1) bringing together participants with different knowledge and skills appropriate for making ergonomic changes such as hourly workers, management representatives and technical specialists such as health and safety, human resources, and skilled trades personnel (Haines et al, 2002;St. Vincent et al, 2006;Van Eerd et al, 2008); and (2) the notion of a "representative participation," model of participatory ergonomics (PE) (Haines et al, 2002: 311-312) wherein personnel on a change team represent their work areas and are directly involved in the change making process.…”
Section: Formation and Training Of The Ergonomic Change Teamsmentioning
confidence: 99%
“…With regard to participatory ergonomics (PE), Eerd et al [4] conducted a literature review that concluded that resources were one of the most frequent reported factors influencing success in PE initiatives. Studies of ergonomic interventions also identify resource allocation to be a barrier for the implementation of ergonomic activities [5,6].…”
Section: Introductionmentioning
confidence: 99%